Impact of Workers Participation on Performance And Productivity: A Systematic literature review - Sonika, (Gyan Management Journal, 2019)
Employees  are the  lifeline  of  an  organization  like the  human  body  needs  blood to  be  alive  as  an  organization needs employees to achieve its goals and to become successful. Workers involved in the  organization in the form of decision making, profit sharing, ownership will be helpful in increasing  their morale and motivation to work so that the organization achieves its goals successfully. It is a  systematic  literature  review;articles  from  the  web  of  science  and  Googlescholar  are  taken  into  consideration. Systematic literature review of all journals and their classification is done according to  different categories and coding is done on the basis of classification. Gaps are found out at last and  conclusions and recommendations for the better study in the future.
Keywords: worker participation; performance; productivity; decision making; ownership